A neuroimaging study of impulsivity in risky and safe drivers - O'Callaghan, Georgia (Trinity College (Dublin, Ireland). School of Psychology, 2016)
Males and individuals under the age of 25 are injured or killed while driving more than other demographic groups. While this overrepresentation is said to be the result of a greater number of aberrant driving behaviours in these groups, it is also noted that not all younger individuals and males engage in risk-taking while driving. Research has demonstrated greater levels of both trait and behavioural impulsiveness in drivers with a history of aberrant driving tendencies, suggesting that heightened impulsivity may be an individual difference factor that contributes to risky driving. The current study aimed to replicate and expand on these findings by including a neuroimaging component. Chapter one puts the research into context by presenting official statistics of collision involvement by age and gender, as well as a review of the factors that are thought to contribute to such collisions. This chapter also explores the literature related to risk taking and impulsivity, with a particular mention of the relationship between heightened impulsivity and aberrant driving behaviours. Chapter two reviews the results of an online survey that was employed to recruit participants for the main study. Demographic information was obtained from survey respondents to identify participants who met the particular age and gender requirements to make up the experimental groups of the main study. These participants were also screened for magnetic resonance imaging (MRI) eligibility and assigned into ‘risky’ and ‘safe’ driver groups based on their self-reported driving history. Chapter two validated the criteria used to differentiate between risky and safe drivers by comparing the amount of aberrant driving behaviours these groups reported on the Manchester Driver Behaviour Questionnaire (DBQ). Eligible participants were recruited to take part in a study that assessed impulsivity using psychometric and behavioural measures, in addition to an investigation of the functional and structural neural correlates of impulsivity using functional magnetic resonance imaging (fMRI) and MRI. Chapter three outlines the overall method and procedure of this study, while chapters four to six separate out a discussion of the results of this experiment by methodology used; psychometric and behavioural measurements of impulsivity (chapter four), fMRI (chapter five) and MRI (chapter six). Each of these subsequent chapters outline the literature pertaining to how these measures relate to the concept of impulsiveness, gender differences on these measures, changes in these measures with age and how they may relate to risk-taking while driving. They will also present and discuss the results of the individual analyses. Finally, chapter seven summarises these findings under three main hypotheses; that impulsivity declines with age, there are gender differences in impulsiveness and impulsivity contributes to aberrant driving, relating each back to the relevant literature and theories mentioned in earlier chapters. As the results of the study provide preliminary evidence that differences in psychometric or behavioural impulsivity between drivers may relate to underlying differences in the structure and/or function of the brain, recommendations are made in this chapter for how future research may study the longitudinal efficacy of cognitive training programs for reducing the impact of impulsivity on aberrant driving.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin